High Level Expert Group Report on Universal Health Coverage for India Instituted by the Planning Commission of India - Planning Commission (Planning Commission, 2010)
The High Level Expert Group [HLEG] on Universal Health Coverage (UHC) was constituted by the Planning Commission of India in October 2010, with the mandate of developing a framework for providing easily accessible and affordable health care to all Indians. While financial protection was the principal objective of this initiative, it was recognised that the delivery of UHC also requires the availability of adequate healthcare infrastructure, skilled health workforce and access to affordable drugs and technologies to ensure the entitled level and quality of care given to every citizen. Further, the design and delivery of health programmes and services call for efficient management systems as well as active engagement of empowered communities.
Planning Commission
Planning Commission